Carcass yield, non-carcass components and economic viability of using licuri oil in the diet for Santa Inês ewe’s - Lima-Cavalcanti, Cinthia P; Tavares-Matos, Maria H; Wischral, Áurea; Souza-Rodrigues, Rafael T; Leal-Araújo, Gherman G; Oliveira-Silva, Elves; Nunes-Nascimento, Paulo V; Menezes-Silva, Dielen J; Domingos-Silva, Alex; Oliveira-Monte, Alane P; Gonçalves-Menezes, Vanúzia; Costa-Gois, Glayciane; et al. (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: The production of biofuels has caused an increase in the prices of agricultural commodities. Thus, the ecological footprint, social inclusion and profitability of production systems have encouraged the use of agroindustrial products as an alternative in ruminant feeds. Objective: To evaluate carcass yields, non-carcass components, and the economic viability of including licuri oil in diet of Santa Ines ewes. Methods: A total of 32 Santa Ines ewes (multiparous, non-lactating, 2–4 years old, and 36.7±0.87 kg of body weight—BW) were allotted to a randomized block design with four treatments (diets containing 0, 2, 4 or 5% licuri oil) with eight replicates per treatment, and confined for 77 days. Results: The incremental inclusion of licuri oil promoted a quadratic response on slaughter BW, carcass and true yields, chest widths, heart fat, pancreas, omental fat, and ribeye area (p<0.05). Carcass, heart and loin weight, shank yield, fat thickness and loin fat were reduced (p<0.05); while cooling losses, left half-carcass weight, saw blade yield, and proportion of meat in the loin increased (p<0.05) with increasing dietary levels of licuri oil. The control diet resulted in the best gross revenue (USD$609.39); however, there was a loss (USD$50.96) regarding economic performance indicators. Conclusion: The use of up to 2% licuri oil in the diet increased carcass yield of discard ewes.